2012
DOI: 10.1063/1.4742990
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nonthermal electron distributions on ion-temperature-gradient driven drift-wave instabilities in electron-ion plasma

Abstract: The effects of nonthermal electron distributions on electrostatic ion-temperature-gradient (ITG) driven drift-wave instabilities in the presence of equilibrium density, temperature, and magnetic field gradients are investigated here. By using Braginskii’s transport equations for ions and Cairns as well as Kappa distribution for electrons, the coupled mode equations are derived. The modified ITG driven modes are derived, and it is found both analytically as well as numerically that the nonthermal distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Through their sensitivity to geometry and material properties, the surface plasmon serves as a local probe of coherent acoustic phonons. In time domain spectroscopy (pump-probe), the pump excites a plasmon which rapidly decays to non-thermalized electrons [5]. The electrons thermalize through scattering processes on a sub picosecond timescale raising the electronic temperature and changing the interband transition rates.…”
Section: Resultsmentioning
confidence: 99%
“…Through their sensitivity to geometry and material properties, the surface plasmon serves as a local probe of coherent acoustic phonons. In time domain spectroscopy (pump-probe), the pump excites a plasmon which rapidly decays to non-thermalized electrons [5]. The electrons thermalize through scattering processes on a sub picosecond timescale raising the electronic temperature and changing the interband transition rates.…”
Section: Resultsmentioning
confidence: 99%
“…[23] Nonthermal electron distributions are also found to affect the linear properties of ITG-driven modes in the presence of magnetic shear. [24] Mirza et al studied the formation of nonlinear vortex structures in ITG mode in the presence of magnetic shear and suprathermal electrons. [25] They found that presence of hotter electrons in the system modify the scale length of vortex structures.…”
Section: Introductionmentioning
confidence: 99%
“…Batool et al. [27] demonstrated the effect of nonthermal electron distribution on ITG driven drift instabilities They found significant modification in ITG driven drift mode due to presence of non-thermal distributed electrons.…”
Section: Introductionmentioning
confidence: 99%